Changes in Green Space Intensity in Újbuda, in Budapest’s 11th district - Jombach, Sandor; N. Hassan, Yaseen; Wagner, Jakab Rudolf; Du , Chenyu; Sölch, Benedek (4D Journal of Landscape Architecture and Garden Art, 2024)
This research uses the ”Green Space Intensity” (GSI) index to describe the changes of green space within Újbuda, Budapest’s 11th district, from 1992 to 2023. The GSI index is based on the Normalized Difference Vegetation Index (NDVI) generated from satellites, but the values have been revised and adjusted to high-resolution orthoimagery and validated by VHR satellite images. The index has been developed over the last two decades, is well known and has been used in the last ten years in research to analyse green spaces within the towns and cities of Hungary. Analysis of green space changes provides reasonable decision-support in urban planning and city development. It helps to define the drivers of change and the effects of changes on the urban climate, paved and built-up areas, the urban habitat of wildlife species and the role of endemic, invasive and ornamental plant species in the city’s green infrastructure. From an urban ecology perspective, this research supports better and more sustainable planning and design solutions. In the 11th district of Budapest, called Újbuda or “New Buda”, using the available Landsat and Sentinel satellite images, we examined changes over three decades. During the first part of the three decades, the increase in green space intensity was more due to the abandonment of former uses and due to the increase in “block of flat” socialist type residential areas built before the 1990s. Meanwhile, several greenfield investment projects resulted in a decrease. For the period after 2015 the decrease in GSI was due to development on abandoned or areas of low land-use intensity, while increases were predominantly associated with the greening and landscaping phase of previous constructions.